Impact of caring for patients with polyhandicap on institutional health care workers’ quality of life: a cross-sectional and longitudinal evaluation - Rousseau, Marie-Christine; Beltran, Any; Hamouda, Ilyes; Aim, Marie-Anastasie; Felce, Agnès; Lind, Katia; Khaldi, Nafissa; El Ouazzani, Houria; Auquier, Pascal; Villemeur, Thierry Billette de; Baumstarck, Karine (Frontiers in Public Health, 2024)
Ethics approval and consent to participate. Regulatory monitoring was performed according to the French law that requires the approval of the French ethics committee (Comité de protection des personnes Sud Méditerranée V, reference no. 2014-A00953-44). A written consent form (from written parental/legal guardian, healthcare workers) was obtained for each participant. Funding. This work was funded by the French Ministry of Social Affairs and Health (Ministère des Affaires sociales et de la Santé, grant no. PREPS-13-0105) and the public health research institute (Institut de Recherche en Santé Publique [IReSP] 2013): The sponsor was represented by University Hospital of Marseille (Assistance publique, Hopitaux de Marseille, France) and its role was to control the appropriateness of ethical and legal considerations. Data avalaibility. In accordance with the French law (French Data Protection Act of 6 January 1978, Commission nationale de l'informatique et des libertés [French DataProtection Authority]) and the General Data Protection Regulation, there are ethical or legal restrictions to sharing data publicly for studies involving human research participant data or other sensitive data. Providing de-identified or anonymized data for specific populations presenting rare conditions, as polyhandicap for example, is not possible even in a minimal dataset. Conclusions derived were drawn from collected data during the period 2020-2021.